Current problems of state policy support to the ukrainians abroad - Кушніренко, О. Г. (Problems of legality, 2013)
Review some of the public policy support relationships with foreign Ukrainians, ways and measures of government and community organizations to further enhance cooperation with foreign Ukrainians.